x-3                            -               3-y     xy-[latex] x^{2} [/latex]                                                   xy-[latex] y^{2} [/latex]

 x-3                            -               3-y      xy-[latex] x^{2} [/latex]                                                   xy-[latex] y^{2} [/latex]
Гость
Ответ(ы) на вопрос:
Гость
[latex]= \frac{x-3}{x(y-x)}- \frac{3-y}{y(x-y)} = \frac{-y(x-3)-x(3-y)}{xy(x-y)}= \frac{-xy+3y-3x+xy}{xy(x-y)}= \\ = \frac{3(y-x)}{xy(x-y)} = \frac{-3}{xy} [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы